La produccion de semilla genetica de frijol - Masaya S., P. (Programa Cooperativo Regional de Frijol para Centroamérica, México y el Caribe (PROFRIJOL), 1989)
The different precautions that should be taken when producing good quality seed are indicated as well as the procedure to maintain intravarietal homogeneity. Seed quality components are (1) purity, that is, no seeds of other var. are included; (2) vigor, which determines germination power and rate; and (3) health (free of pathogens). Maintaining a var. implies planting lots where a new selection is made of those individual plants that maintain visually recognizable characteristics considered typical of the var., such as color of the stem, hypocotyl, and flower; pod color and shape; and plant architecture, among others. The breeder or breeding program is responsible for the production of good quality seed; this process must be continuous in order to produce improved seed at least every 3 or 4 yr. (CIAT)